Morfologia comparativa e distribuição batimétrica de duas espécies de Ophiuroidea, na região costeira de Ubatuba - Monteiro, Ana Maria Gouveia [UNESP]; Reis, Margarete de Oliveira [UNESP]; Pardo, Érica Verónica [UNESP] (Universidade de São Paulo (USP), Instituto Oceanográfico, 1992)
Durante o período de outubro de 1985 a julho de 1987, foram coletados 722 ofíuróides pertencentes às espécies Ophioderma januarii e Ophioplocus januarii, na costa do Estado de São Paulo. Realizou-se medidas do diâmetro do disco dos exemplares e estas variaram entre 10,5 e 21,5 mm para Ophioderma januarii e entre 2,6 e 21,5 mm, para Ophioplocus januarii. Foram efetuadas observações das características morfológicas externas dos indivíduos e posteriormente, organizadas séries de crescimento, com o intuito de evidenciar possíveis alterações. Verificou-se para Ophioderma januarii, variações na forma dos escudos, no número de papilas orais e de espinhos braquiais, na coloração da superfície dorsal do disco e das placas braquiais dorsais e para Ophioplocus januarii variações nas escamas primárias, na série de escamas maiores da região interradial dorsal do disco, no número de escamas entre a centro-dorsal e a margem do disco, na forma dos escudos radiais e orais, no número de papilas orais, na coloração da superfície dorsal do disco e das placas braquiais dorsais. O resultado das análises de parâmetros ambientais dos locais de coleta, mostrou que as duas espécies ocorreram em áreas com condições ambientais distintas. Ophioderma januarii foi amostrada na região costeira até 36 m de profundidade e Ophioplocus januarii entre 30 e 100 m.

A total of 722 ophiuroids belonging to the species Ophioderma januarii and Ophioplocus januarii was collected on the coast of the State of São Paulo, from October 1985 to July 1987. Measurements of disc diameter of the specimens were ranged from 10,5 to 21,5 mm for Ophioderma januarii and from 2,6 to 21,5 mm for Ophioplocus januarii External morphological characteristics of the individuals were observed and growth series were organized to detect possible changes. For Ophioderma januarii variations were found in the shape of the shields, in the number of oral papillas and arms spines, in the color of the dorsal disc surface and in the dorsal arm plates. on Ophioplocus januarii variations were found in primary scales, in the major scales series of the dorsal interradial region of the disc, in the number of scales between the central plate and the edge of the disc, in the shape of the radiais and orals shields, in the number of the oral papillas, in the color of the dorsal disc surface and in the dorsal arm plates. Analyses of environmental parameters show that both species were present in areas with distinct environmental conditions. Ophioderma januarii was collected in the coastal region and as far as 36 m deep and Ophioplocus januarii from 30 to 100 m deep.
Comparative morphology and bathymetric distribution of two species of Ophiuroidea from coastal region of Ubatuba
Keywords: Morfologia; Distribuição vertical; Fatores abióticos; Ophiuroidea; Ophioderma januarii; Ophioplocus januarii; Ubatuba: SP; Brasil; Morphology; Vertical distribution; Abiotic factors; Ophiuroidea; Ophioderma januarii; Ophioplocus januarii; Ubatuba: SP; Brazil